LandScape Corridors (lscorridors): a new software package for modelling ecological corridors based on landscape patterns and species requirements - Ribeiro, John Wesley [UNESP]; Silveira dos Santos, Juliana [UNESP]; Dodonov, Pavel; Martello, Felipe [UNESP]; Brandão Niebuhr, Bernardo [UNESP]; Ribeiro, Milton Cezar [UNESP] (Wiley, 2017)
Maintaining connectivity is one of the main challenges for biodiversity conservation world-wide. Ecological corridors are important to maintain landscape connectivity, but their efficiency depends on landscape patterns and species responses at different spatial extents and landscape contexts. We developed a new ecologically oriented free software package, LandScape Corridors (lscorridors), to improve ecological corridor design by considering biodiversity responses to landscape attributes at a variety of spatial extents. LandScape Corridors considers stochastic variation, species perception and landscape influence on organisms in the design of ecological corridors. In addition to the least cost path algorithm, we propose four different methods for the simulation of multiple-path functional ecological corridors. One method uses the information for each pixel separately, whereas the three other methods permit corridor simulation considering the landscape context at different spatial extents. LandScape Corridors permits to simulate corridors for species with different requirements and considers that different species perceive and respond to the surrounding landscape in different ways, as many species may choose to move through areas that may not be the most permeable ones in the landscape. Two parameters in lscorridors modulate the stochasticity in corridors simulations. The first parameter is the level of variability added to the input resistance map in each simulation, resulting in more variable and spatially spread-out corridors. The other parameter is the spatial extent that may influence each pixel; larger extents result in larger spatial zones affecting each pixel during corridors simulations. In addition, when considering spatial influence, the simulations may be performed for species highly, medially or less sensitive to habitat quality. Some currently available software are not free or depend on a paid GIS software to work. In addition, some software do not support large matrices in their simulations, limiting their use. LandScape Corridors is designed to deal with large rasters, is based on strictly freeware software, and is freely available online. This allows the users to implement new methods for modelling multi-scale and ecologically based corridors. LandScape Corridors is a potential tool for the identification of protected areas, as corridor simulation considers species movement and landscape connectivity, essential characteristics to aid in large-scale biodiversity conservation, especially in anthropogenic landscapes. LandScape Corridors provides what we may call a zone for conservation, showing a set of connected areas in the landscape which may be ordered according to their potential for ecological corridors or which may be used as an aid for conservation strategies or ecological restoration projects.
Keywords: corridor modelling; landscape connectivity; landscape ecology; matrix permeability; species perception